Uncrewed Surface Vessel Technological Diffusion Depends on Cross-Sectoral Investment in Open-Ocean Archetypes: A Systematic Review of USV Applications and Drivers - Patterson, Ruth G.; Lawson, Emily; Udyawer, Vinay; Brassington, Gary B.; Groom, Rachel A.; Campbell, Hamish A. (Frontiers in Marine Science, 2022)
Accessing the world’s oceans is essential for monitoring and sustainable management of the maritime domain. Difficulty in reaching remote locations has resulted in sparse coverage, undermining our capacity to deter illegal activities and gather data for physical and biological processes. Uncrewed Surface Vessels (USVs) have existed for over two decades and offer the potential to overcome difficulties associated with monitoring and surveillance in remote regions. However, they are not yet an integral component of maritime infrastructure. We analyse 15 years of USV-related literature to determine the factors limiting technological diffusion into everyday maritime operations. We systematically categorised over 1,000 USV-related publications to determine how government, academia and industry sectors use USVs and what drives their uptake. We found a striking overlap between these sectors for 11 applications and nine drivers. Low cost was a consistent and central driver for USV uptake across the three sectors. Product compatibility and lack of complexity appear to be major factors limiting USV technological diffusion amongst early adopters. We found that the majority (21 of 27) of commercially available USVs lacked the complexity required for multiple applications in beyond the horizon operations. We argue that the best value for money to advance USV uptake is for designs that offer cross-disciplinary applications and the ability to operate in an unsheltered open ocean without an escort or mothership. The benefits from this technological advancement can excel under existing collaborative governance frameworks and are most significant for remote and developing maritime nations.